12th Gawad CCP para sa alternatibong pelikula at video - Ruiz, Joel (Animo Repository, 1999)
In the 12th Gawad CCP para sa Alternatibong Pelikula at Video, the team of Joel Ruiz and Stephen Ku won 2nd prize in the short video feature category. Mula Sabado tells the story of three young adults whose lives intertwined in a span of three days.